The Test of Alcohol Distallation Equipment from A Mix of Palm Sap with Coconut Shell Charcoal and Lime - Giarman Giarman (International Journal of Mechanical Computational and Manufacturing Research, 2022)
Palm sap is a sweet liquid obtained from the sugar palm plant (Arenga pinnata MEER) by cutting the flower stalk. Generally, palm sap is widely used for the manufacture of brown sugar, fresh drink of palm sap (saguer), vinegar and alcoholic beverages. The testing procedure carried out is as follows: Beginning of the test 1. Recording the air temperature 2. Recording the temperature of the water and palm sap 3. Heating is done using a kerosene stove with an estimated temperature of up to 100 C boiling. A total of 5 liters of palm sap raw material is put into the heating tank which is flowed through the top hole by opening the cover, accompanied by filling water in the heating tank. On checking the level of purity with the influence of coconut shell charcoal powder as an absorbent on palm sap alcohol, it was seen that there was an effect in increasing alcohol content. However, it cannot be completely absorbed considering that the coconut shell charcoal used is not active coconut shell charcoal. To produce a good level of alcohol purity (80%) a good mixture ratio is 150 grams: 50 grams of coconut shell charcoal and lime. The efficiency of distalization is 83%. 50 grams of coconut shell charcoal and lime. The efficiency of distalization is 83%. 50 grams of coconut shell charcoal and lime. The efficiency of distalization is 83%.